PENGARUH PEMBERIAN TEPUNG KANGKUNG AIR (Ipomoea aquatica Forsk.) FERMENTASI TERHADAP KARKAS DAN ORGAN PENCERNAAN AYAM KAMPUNG SUPER - Lisnawaty Silitonga; Paulini Paulini; Iis Yuanita; Siti Ma'rifah; Marta Tio Silaban (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2024)
This study aimed to investigate the effects of fermented water spinach (Ipomoea aquatica forsk) flour supplementation on super-native chickens' carcasses and digestive organs. The material utilized consisted of water spinach flour subjected to 14 days of anaerobic fermentation, which was then incorporated into the diet. The experimental design employed was a Completely Randomized Design (CRD) with 4 treatments, each replicated 6 times. The treatments included: P0 (basal diet), P1 (3% fermented water spinach flour), P2 (6% fermented water spinach flour), and P3 (9% fermented water spinach flour). Results showed that supplementation with fermented water spinach flour did not significantly affect super-native chickens' carcasses and digestive organs (P>0.05). However, numerically, supplementation with up to 9% fermented water spinach flour showed promising results on the carcass and digestive organs of super native chickens, suggesting its potential as a protein source substitute for tofu waste in feed formulations.